The Ccr4‐Not complex is a key regulator of eukaryotic gene expression. (29th January 2016) - Collart, Martine A.
Abstract : The Ccr4‐Not complex is a multisubunit complex present in all eukaryotes that contributes to regulate gene expression at all steps, from production of messenger RNAs (mRNAs) in the nucleus to their degradation in the cytoplasm. In the nucleus it influences the post‐translational modifications of the chromatin template that has to be remodeled for transcription, it is present at sites of transcription and associates with transcription factors as well as with the elongating polymerase, it interacts with the factors that prepare the new transcript for export to the cytoplasm and finally is important for nuclear quality control and influences mRNA export. In the cytoplasm it is present in polysomes where mRNAs are translated and in RNA granules where mRNAs will be redirected upon inhibition of translation. It influences mRNA translatability, and is needed during translation, on one hand for co‐translational protein interactions and on the other hand to preserve translation that stalls. It is one of the relevant players during co‐translational quality control. It also interacts with factors that will repress translation or induce mRNA decapping when recruited to the translating template. Finally, Ccr4‐Not carries deadenylating enzymes and is a key player in mRNA decay, generic mRNA decay that follows normal translation termination, co‐translational mRNA decay of transcripts on which the ribosomes stall durably or which carry a non‐sense mutation and finally mRNA decay that is induced by external signaling for a change in genetic programming. Ccr4‐Not is a master regulator of eukaryotic gene expression. WIREs RNA 2016, 7:438–454. doi: 10.1002/wrna.1332 This article is categorized under: Translation > Translation Regulation RNA Turnover and Surveillance > Turnover/Surveillance Mechanisms RNA Turnover and Surveillance > Regulation of RNA Stability